Discovery of a companion at the brown dwarf limit to the solar‐type star Gliese 29. Issue 6 (June 2016) - Chini, R.; Fuhrmann, K.; Pozo Nuñez, F.; Ramolla, M.; Kaderhandt, L.; Niedworok, N.; Hodapp, K.‐W.
Abstract: Gliese 29 is a 7 to 8 Gyr old, southern Population I turnoff star with a large proper motion of 1″/yr. Using recent direct imaging observations with the 0.8 m Infrared Imaging System (IRIS) of the Universitätssternwarte Bochum near Cerro Armazones in Chile, we demonstrate that the faint source 2MASS J00402651–5927168 at a projected angular separation ρ = 6.″35 is a common‐proper‐motion companion to Gl 29. Provided this source is not part of a further subsystem, the IRIS J ‐ and K s ‐band photometry either implies a spectral type of about L2, based on its absolute magnitude, or an approximate mass M B ≃ 0.077 M⊙, suggesting that it may even be a brown dwarf. Assuming a face‐on circular orbit this faint companion orbits Gl 29 in 1880 years. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)